Analisis Klausa dalam Teks Prosedur pada Buku Bahasa Indonesia Kelas VII SMP Kurikulum Merdeka - Sunaryo Sunaryo; Ikhwan Abdul Aziz; Rizqi Aji Wirastomo; Arif Mansurrudin; Wahyu Hari Winarno; Asep Purwo Yudi Utomo (Pusat Riset dan Inovasi Nasional, 2023)
The syntax studied has three scopes: phrases, clauses, and sentences. There are many problems regarding how to differentiate and classify clauses. Not a few equate between phrases and clauses. A collection of several words contains a clause if some of these words have subject and predicate elements, while a phrase means several words consisting of at least one predicate element without any subject element or can be said to be the opposite of a clause. The purpose of this article is to share knowledge about the grouping of clauses and provide examples of each sentence in the procedure text so that the benefits based on this analysis are expected to open and increase knowledge and broaden horizons for writers and readers so that readers can interpret and classify clauses based on analysis. the syntax. The results of the analysis in this article are expected to be useful for students and the wider community regarding language learning because it provides a lot of knowledge related to the grouping of clauses and the types of clauses in procedure texts in Buku Bahasa Indonesia Kelas VII SMP Kurikulum Merdeka. In the research context, methods and methodology are described and will be explained through a qualitative descriptive methodological approach. Qualitative methods aim to seek an in-depth understanding of symptoms and facts.